DAYA HAMBAT EKSTRAK Eucheuma spinosum DENGAN KONSENTRASI BERBEDA TERHADAP Bacillus cereus - Madyasta Anggana Rarassari; Darius Darius; Hartati Kartikaningsih (Faculty of Science and Technology University Ibrahimy, 2016)
Eucheuma spinosum is one phylum of red algae, that can be used as a natural antibacterial. Indicator bacteria used were Bacillus cereus causes food spoilage. How to handle with antibotic, but the bacteria to become resistant. Therefore, it takes effort to get the antibacterial from natural material. The purpose of this study to get the best concentration of the Eucheuma spinosum extract to inhibit Bacillus cereus and obtain bioactive compounds contained in Eucheuma spinosum. Treatment concentration of 400 ppm, 800 ppm and 1600 ppm with 4 replications.Analysis of the test data using a completely randomized design factorial with a differentiator (Test F). The results produced the best antibacterial from Eucheuma spinosum extract with a concentration of 800 ppm. This is indicated by the average diameter of inhibition zone against Bacillus cereus in Eucheuma spinosum extract with a concentration of 800 ppm is 1,73 mm. While the results of the analysis by GC-MS methods allegedly contained 9 antibacterial compounds extracted from Eucheuma spinosum, such as Phenol, Eugenol, Pentadecane, Heptadecane, 3- Eicosene, 9- Eicosene, 1- Hexadecane, Docosane dan 1- Octadecene.